Reimagining Digital Identity Management: A Critical Review of Blockchain-Based Identity and Access Management (IAM) Systems - Architectures, Security Mechanisms, and Industry-Specific Applications (Advances in Deep Learning Techniques, 2021)
The ever-expanding digital landscape, characterized by the relentless proliferation of online services and applications, has firmly established digital identities as the cornerstone of secure interactions in our contemporary world. However, the efficacy of these interactions hinges on the robustness of the underlying Identity and Access Management (IAM) systems that safeguard them. Traditional, centralized IAM solutions, while serving as the bedrock of digital identity management for decades, are increasingly under fire for their susceptibility to data breaches and inherent privacy limitations. This paper presents a comprehensive exploration of blockchain-enabled IAM systems, investigating their potential to revolutionize the paradigm of digital identity management. We embark on a meticulous dissection of the architectural foundations of blockchain-based IAM, meticulously dissecting their distributed ledger structure, the intricacies of employed consensus mechanisms, and the cryptographic primitives that safeguard information integrity.Following this in-depth architectural exploration, a rigorous examination of the security features woven into these systems is presented. This analysis encompasses tamper-proof data storage mechanisms, the implementation of granular access control models that enable fine-tuned permission structures, and user-centric privacy preservation techniques that empower individuals with unprecedented control over their digital identities. To illuminate the practical value proposition of blockchain-based IAM, we delve into its application across diverse industry verticals. This includes exploring its transformative potential in e-governance by facilitating secure, transparent, and efficient citizen-government interactions. We investigate its role in the healthcare sector, enabling secure, auditable, and interoperable patient data management, fostering a more streamlined and patient-centric healthcare ecosystem. Furthermore, the paper examines its utility within the financial domain, fostering secure, efficient, and auditable financial transactions. Finally, we explore its burgeoning application within the realm of the Internet of Things (IoT), providing a foundation for secure device authentication and authorization within interconnected ecosystems, thus paving the way for the development of a truly secure and trustworthy IoT landscape.The paper concludes with a critical evaluation of the current challenges and lacunae in research, charting a course for future advancements in this dynamic domain.
Keywords: Blockchain Technology; Decentralized Identity; Self-Sovereign Identity (SSI); Distributed Ledger Technology (DLT); Cryptographic Primitives; Access Control; Privacy-Preserving Techniques; E-governance; Healthcare; Financial Services; Internet of Things (IoT)